Prospects for the Caribbean sugar industries into the twenty-first century - Blades, Hayden ([CARICOM Secretariat] [Georgetown]GY, 1994)
Reviews the role, contribution and performance of the sugar industry in the Caribbean Community. Provides an overview of the world sugar economy and an analysis of the markets and marketing arrangements for sugar produced within the Caribbean Community. Presents technological developments impacting Caribbean sugar industries. Submits proposals and strategies for the long-term development of the sugar industry.